Current status of the threatened Olrog's Gull Larus atlanticus: global population breeding distribution and threats - Yorio, Pablo Martin (2013)
The Olrog's Gull Larus atlanticus breeds only in Argentina and is currently categorized as Vulnerable. Knowledge of the location of colonies and an updated understanding of human activities that may impact their breeding populations is crucial to the development of adequate conservation and management actions. In this paper we update of the breeding distribution and abundance of the threatened Olrog's Gull, using information from three aerial surveys (2004, 2007 and 2009) in its main breeding area, Buenos Aires Province, complemented with additional nest counts at locations throughout its breeding distributional range. We also provide an updated and more detailed account of threats faced by Olrog's Gulls at their nesting grounds, and information on the progress made towards their protection. The number breeding sites ranged from 7-12 per year, with their locations differing among years. Five previously unrecorded breeding locations were identified. Colony size ranged from 5-3,540 breeding pairs, with the total breeding population 4,860-7,790 pairs, 98% of which nest in southern Buenos Aires. The main threats faced by breeding Olrog's Gulls include coastal development, pollution, sport fishing and unregulated tourism and recreational activities. The recent strengthening of the protected area system in Argentina has resulted in all known breeding sites with the exception of Isla Brightman now falling within protected areas. We need comprehensive, simultaneous surveys throughout the breeding range to track global population trends. Despite enhanced protection of Olrog's Gull breeding populations, efforts are still needed to ensure that guidelines for their protection are included in management plans and that these are implemented effectively.